Investigation of the Spiritual Care Effects on Anxiety, Depression, Psychological Distress and Spiritual Levels of Turkish Muslim Radiotherapy Patients - Şirin, Turgay (Journal of religion and health, 2021)
The aim of this study is to examine the spiritual care support given to Muslim cancer patients undergoing radiotherapy with an experimental study on the spirituality, anxiety, depression and distress levels of these patients. In this study, experimental research design with experimental control group was used. Personal information form designed by researchers, HAD scale, DT scale and Spirituality Scale was used for personal information. In conclusion, it was determined that the support for Islamic spiritual care had positive effects on hospitalized radiotherapy patients. According to the results obtained, it is recommended to examine in larger sample groups in different treatment programs in order to reveal the effect of spiritual care support.